2022
DOI: 10.1111/1365-2745.14047
|View full text |Cite
|
Sign up to set email alerts
|

Herbarium records provide reliable phenology estimates in the understudied tropics

Abstract: 1. Plant phenology has been shifting dramatically in response to climate change, a shift that may have significant and widespread ecological consequences. Of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…However, invaders can capitalize on vacant temporal niches regardless of when they occur—indeed, several invasive species have also been found to benefit from comparatively later phenological activity (Gerlach & Rice, 2003; Pearson et al., 2012; Resasco et al., 2007; Xu et al., 2007). Further, though phenology is often treated as a linear progression of events through time in temperate regions, this is not the case in many areas of the world with milder or less seasonally variable climates, such as non‐resting tropical systems (Davis et al., 2022; Mendoza et al., 2017; Park, Lyra, et al., 2023; Staggemeier et al., 2010, 2020). Though California does have a seasonal climate, it is comparatively warm year‐round, and temperatures rarely drop below freezing in the low‐elevation coastal regions of the state where non‐native species richness is highest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, invaders can capitalize on vacant temporal niches regardless of when they occur—indeed, several invasive species have also been found to benefit from comparatively later phenological activity (Gerlach & Rice, 2003; Pearson et al., 2012; Resasco et al., 2007; Xu et al., 2007). Further, though phenology is often treated as a linear progression of events through time in temperate regions, this is not the case in many areas of the world with milder or less seasonally variable climates, such as non‐resting tropical systems (Davis et al., 2022; Mendoza et al., 2017; Park, Lyra, et al., 2023; Staggemeier et al., 2010, 2020). Though California does have a seasonal climate, it is comparatively warm year‐round, and temperatures rarely drop below freezing in the low‐elevation coastal regions of the state where non‐native species richness is highest.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of flowering and germination, leaf‐out, and fruiting are determined at least partially by environmental conditions that are affected by climate change (Wolkovich et al., 2013). As phenological responses to changes in climate can vary within and among species (Park et al., 2022; Park, Lyra, et al., 2023; Xie et al., 2022), global warming will likely alter the degree of phenological similarity between native and non‐native species. On the one hand, it has been suggested that non‐native species, invasive ones in particular, shift flowering time more than native species in response to warming and this can correlate with increases in abundance (Willis et al., 2010; Wolkovich et al., 2013; Zettlemoyer et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, just as most phenological studies have been done in the northern hemisphere, more have undoubtedly been conducted in temperate rather than tropical ecosystems. Park et al (2023) show that herbarium specimens from Brazil, because they typically represent a much broader sampling across geographic and climatic space than do field observational data, can be a better source of data to test phenological hypotheses. The data already reside in herbaria, and phenological estimates from herbarium specimens align well with those collected in the field.…”
Section: The Impacts Of Global Change On Phenologymentioning
confidence: 99%
“…Unsurprisingly, the biodiversity data compiled by different and uncoordinated initiatives (Feng et al., 2022) are almost always characterized by the pervasive existence of taxonomical and geographical biases and shortcomings (see, for example, Hortal et al., 2015; Hughes et al., 2021; Meyer et al., 2016; or Larsen & Shirey, 2021). These drawbacks, inherent to opportunistically collected historical occurrence data, may limit but not invalidate the use of such information for scientific or conservation purposes (Grand et al., 2007; Isaac et al., 2014; Park, Lyra, et al., 2023; Park, Xie, et al., 2023; van Strien et al., 2013). Different approaches to filtering and processing information from biodiversity databases have allowed taking advantage of this unprecedented source of information to propose explanatory hypotheses about the spatiotemporal distributions of organisms (Belitz et al., 2020; Di Cecco et al., 2023; García‐Roselló et al., 2015; Heberling et al., 2021; Isaac et al., 2014; Lajeunesse & Fourcade, 2023; Pagel et al., 2014).…”
Section: Introductionmentioning
confidence: 99%